How internet helped firms cope with COVID-19 - Joël Cariolle; Florian Léon (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
This paper questions whether familiarity with digital technologies helped firms cope with the COVID-19 pandemic. Using data on 31,387 firms from 39 developing and developed economies, our results stress that businesses using website before the crisis showed higher absorption capacities than other firms during the crisis. The positive role of website use was mainly through the adoption of coping strategies, in particular home-delivery services, online sales or remote work. In contrast, the positive effect played by the prior use of internet is not explained by better access to external public (government support) or private (bank loan) financial resources.
Keywords: 330